A randomized trial of iron- and zinc-biofortified pearl millet-based complementary feeding in children aged 12 to 18 months living in urban slums - Mehta, Saurabh; Huey, Samantha L.; Ghugre, Padmini S.; Potdar; Ramesh D.; Venkatramanan, Sudha; Krisher, Jesse T.; Ruth, Caleb J.; Chopra, Harsha V.; Thorat, Aparna; Thakker, Varsha; Johnson, Lynn; Powis, Laura; et al. (Elsevier, 2022)
Background & aims: Biofortification of staple crops with higher levels of micronutrients via traditional breeding methods is a sustainable strategy and can possibly complement fortification and other interventions to target micronutrient deficiencies in low resource settings, particularly among vulnerable populations such as children. We aimed to determine if iron- and zinc-biofortified pearl millet (FeZnPM, Dhanashakti, ICTP-8203Fe)-based complementary feeding improves nutritional status, including iron biomarkers and growth, in children living in urban slums of Mumbai. Methods: We conducted a randomized controlled trial of FeZnPM among 223 children aged 12e18 months who were not severely anemic at baseline (hemoglobin 9.0 g/dL). Children were randomized to receive either FeZnPM or conventional non-biofortified pearl millet (CPM) daily for 9 months. Iron status (hemoglobin, serum ferritin), plasma zinc, and anthropometric indicators (length, weight, mid-upper arm circumference, triceps and subscapular skinfolds) were evaluated at enrollment and throughout the trial. World Health Organization (WHO) anthropometric z-scores were calculated using WHO growth standards. Primary outcomes were hemoglobin and serum ferritin concentrations, and growth, defined as WHO z-scores. An intent to treat approach was used for analyses. We used the Hodges-Lehmann-Sen test to assess the change in primary outcomes between baseline and the last visit and report corresponding 95% confidence intervals. Results: At baseline, 67.7% of children were anemic (hemoglobin <11.0 g/dL) and 59.6% were iron deficient (serum ferritin <12.0 mg/L). FeZnPM did not significantly increase iron biomarkers or improve growth, compared to CPM. In subgroup analyses, FeZnPM improved hemoglobin concentrations in male children, and in children with iron deficiency or iron depletion (serum ferritin <25.0 mg/L) at baseline, relative to CPM. Conclusions: Daily consumption of FeZnPM-based complementary foods did not significantly impact iron and zinc status or growth in children living in Mumbai's urban slums. However, the intervention